(untitled) - Falco, Liliana; Coviella, Carlos (Universidad Nacional de Cuyo. Facultad de Ciencias Agrarias)

Contribution of Amynthas gracilis (Megascolecidae) and Octolasion cyaneum (Lumbricidae) to soil physical stability : a mesocosm experiment (2016)
The contribution of the introduced species Amynthas gracilis (Kinberg, 1867) and Octolasion cyaneum (Savigny, 1826) to the physical stability of the soil was evaluated in a mesocosm experiment. Pore formation and stable aggregates were measured; as well as changes in bulk density, porosity, and soil moisture. Mesocosm pots were organized into three treatments: 1- soil + Amynthas gracilis, 2- soil + Octolasion cyaneum and 3- soil (control containers). The experiment ran for 13 weeks and it was conducted in controlled conditions in a greenhouse. At the end of the experiment both treatments with earthworms had higher number of pores and stable aggregates at the two considered depths (0 - 5 cm and 5 - 10 cm). The presence of both earthworm species favors the formation of a significantly higher proportion of stable aggregates larger than 5 mm (60%), when compared to the control without worms. These structures helped maintaining bulk density and porosity and improved water circulation. The results show that when compared to the control, both treatments had a lower loss of pore space, lower bulk density, and higher soil moisture, all attributable to earthworm presence. It is concluded that, despite both being introduced species, in intensive agricultural systems, A. gracilis and O. cyaneum can contribute to the maintenance of soil physical stability thus helping to preserve the sustainability of agro-ecosystems, even if native species became rare or locally extinct.